1998
DOI: 10.1083/jcb.143.4.901
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Function of Hsp90 Is Dependent on ATP Binding and ATP Hydrolysis

Abstract: Heat shock protein 90 (Hsp90), an abundant molecular chaperone in the eukaryotic cytosol, is involved in the folding of a set of cell regulatory proteins and in the re-folding of stress-denatured polypeptides. The basic mechanism of action of Hsp90 is not yet understood. In particular, it has been debated whether Hsp90 function is ATP dependent. A recent crystal structure of the NH2-terminal domain of yeast Hsp90 established the presence of a conserved nucleotide binding site that is identical with the binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
511
7
15

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 552 publications
(545 citation statements)
references
References 64 publications
(132 reference statements)
12
511
7
15
Order By: Relevance
“…Although Hsp90 is the direct target of GA and its clinically relevant derivatives, inhibition of Hsp90's relatively weak ATPase activity itself is unlikely to be useful as a pharmacodynamic endpoint of drug therapy in patients. 44 Hsp90 activity can be assessed in tumor samples indirectly by evaluating changes in levels of client proteins that are regulated by Hsp90. The functions of numerous cancer-associated proteins are regulated by Hsp90 and are altered by Hsp90 inhibitors, [45][46][47][48] but it is not yet clear which of the affected proteins will be most predictive of activity against a particular tumor type in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Although Hsp90 is the direct target of GA and its clinically relevant derivatives, inhibition of Hsp90's relatively weak ATPase activity itself is unlikely to be useful as a pharmacodynamic endpoint of drug therapy in patients. 44 Hsp90 activity can be assessed in tumor samples indirectly by evaluating changes in levels of client proteins that are regulated by Hsp90. The functions of numerous cancer-associated proteins are regulated by Hsp90 and are altered by Hsp90 inhibitors, [45][46][47][48] but it is not yet clear which of the affected proteins will be most predictive of activity against a particular tumor type in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The chaperone activity of HSP90 is inhibited by ansamycin antibiotics (GA) [18]. Recently, it has been published that the in i o function of HSP90 is dependent on ATP binding and ATP hydrolysis [21,22]. Furthermore, an important result has been reported that HSP90 acts as a capacitor for morphological evolution [41].…”
Section: Discussionmentioning
confidence: 99%
“…The chaperone activity was suppressed almost completely at a molar ratio of 1 : 10 (HSP90 : CDDP). The CDDP concentration (1n5 µM) is lower than that of the GA concentration (18 µM) which inhibits the ATPase activity of HSP90 almost completely [21]. Next, we investigated the influence of Mg\ATP on this assay system.…”
Section: Figure 5 Effect Of Cddp On the Chaperone Activity Of Hsp90mentioning
confidence: 99%
See 1 more Smart Citation
“…27,28 These agents disrupt HSP90 association with client proteins by occupying the nucleotide-binding site of HSP90, [29][30][31] therefore, preventing binding of HSP90 with ATP and affecting the composition of HSP90 containing multimolecular chaperone complexes. 32, 33 In view of evidence of activity in preclinical animal models, 34 …”
Section: Discussionmentioning
confidence: 99%